A case of midgut malrotation in an adult male causing volvulus and subacute intestinal obstruction - Vijayalakshmi, V.; M. S., K. Amilthan; S., Karthikeyan (International Surgery Journal, 2019)
Small bowel malrotation is a congenital disorder of midgut rotation usually encountered in paediatric age group. Here is a case report of small bowel sub-acute obstruction due to midgut volvulus precipitated by malrotation. The incidence of microtonal presentation in adults is 0.2%, making this case a rarity. This patient presented with chronic vague symptoms like dyspepsia, diffuse low-grade abdominal pain, non-projectile vomiting which were on and off for 4 to 5 years since he presented to us. Furthermore because of the remitting nature of his symptoms, these symptoms usually pointed out to a more benign ailment, so unless we do a more elaborate study like computed tomography, we might miss the diagnosis. This case report emphasis the wide range of presenting age for certain congenital disorders like malrotation of gut.